Management of a 30-year-old pregnant patient with carcinoma breast posted for mastectomy managed by Thoracic Epidural - V Abraham; AG Verghese; Melchisedec; Ria; Neenu (Global Journal of Anesthesiology - Peertechz Publications, 2023)
Pregnancy, in itself, is a high-risk condition and any procedures performed during any gestation period can prove detrimental for the mother as well as the fetus, hence it becomes a challenge for the anesthetist to choose a mode of anesthesia that can prevent major complications. We witnessed a similar case in our hospital wherein a 30-year-old pregnant patient at 34 weeks gestation with carcinoma breast was posted for mastectomy. Considering all the risks, we managed this case by thoracic epidural successfully. The surgery was uneventful.